Performance Analysis in Gigabit Passive Optical Networks - Dogan, Bilal; Unverdi, N. Ozlem (IEEE, 2024)
The effects of optical filters and optical power dividers, which are commonly utilized in passive optical network designs, on data transmission quality were studied. Data transmission quality for systems having various types of optical filters was compared with that of a filterless one. An optical power divider with a split ratio of 1:2, 1:4, or 1:8 was utilized in the field cabinet. The designs with various power division ratios while keeping the other parameters constant were generated with the OptiSystem 7.0 simulation software. Depending on the division ratio, the optical signal attenuation at the input and output of the power divider was compared both theoretically and practically.
Keywords: Communication technologies; passive optical network; optical filter; splitter; GPON; Computer Science; Engineering; Telecommunications